Analysis Of Bank Muamalat's Service Products: Innovation And Impact On Local Economy Bank Muamalat Kcp Serdang, Medan - Syafitri, Nikita Adelia; Amelia, Nova; Abdullah, Abdul; Nasution, Muhammad Nabil (Universitas Muhammadiyah Sumatera Utara, 2025)
This study aims to analyze the service products offered by Bank Muamalat Indonesia, the first Islamic bank in Indonesia. The research method used is a literature study and secondary data analysis from reliable sources. The results indicate that digital service innovations and Islamic financial products provided by Bank Muamalat have a positive impact on local economic growth and increase public trust in the Islamic banking system. However, the bank faces challenges, including fierce competition with conventional banks and the necessity to continuously enhance digital services. Furthermore, this study highlights the role of Bank Muamalat in promoting financial inclusion by offering various Sharia-compliant products such as savings accounts, financing services, and digital banking solutions. The findings suggest that the bank’s adoption of technology, particularly through mobile banking, significantly enhances customer accessibility and satisfaction. Additionally, Bank Muamalat’s financing schemes contribute to the development of Micro, Small, and Medium Enterprises (MSMEs), strengthening their role in the broader economic landscape. Despite its achievements, the bank must address several challenges, such as increasing awareness of Islamic financial principles, adapting to technological advancements, and sustaining customer trust in a highly competitive market. This study provides insights into how Islamic banking institutions can leverage innovation to sustain growth and remain relevant in the evolving financial sector.Keywords: Islamic banking, Bank Muamalat, service products, digital innovation, local economy, financial inclusion, MSMEs.